Optimization of sustainable buildings envelopes for extensive sheep farming through the use of dynamic energy simulation - Maria Elena Menconi; David Grohmann (Journal of Agricultural Engineering, 2013)
Extensive sheep farming can be seen as a marginal market, compared to other livestock and agricultural activities, taking into account only the economic absolute values. But for many rural marginal areas within the European Community member states, in particular for those located in the Mediterranean area on hills or mountains with high landscape value, extensive sheep farming is not only the longest practiced animal farming activity, but also the most interesting considering its adaptability to the territorial morphology and the restrictions that have been established over the years in terms of sustainable rural development practices. At the moment, most of the structures used in this type of farming are built using low cost and sometimes recycled, but often unsuitable, materials. Few specific studies have been carried out on this particular issue assuming, presumably, that the very low profit margins of these activities made impossible any restructuring. Taken this into account, the new Rural Development Plans that will be issued in 2014 will surely contain some measure dedicated to innovations in farming structures and technology towards facilitating the application of the principles of energy optimization. This is the framework in which the present research has developed. The software that has been applied to perform the energy optimization analysis is the dynamic energy simulation engine Energy Plus. A case study farm has been identified in the small village of Ceseggi (PG), situated in Central Italy. For the case study optimum thermo hygrometric conditions have been identified to ensure the welfare of animals and operators and it has been hypothesized the insertion of an ideal HVAC system to achieve them. Afterwards were evaluated the different energy requirements of the building while varying the insulation material used on the vertical surfaces. The greater goal is to verify which could be the best insulation material for vertical surfaces from energy requirement, primary energy and cost points of view and to verify as well if it would be possible to achieve optimum environmental conditions by using only passive solutions.